1985
DOI: 10.1161/01.atv.5.4.336
|View full text |Cite
|
Sign up to set email alerts
|

Structural and hemodynamic response of peripheral arteries of macaque monkeys to atherogenic diet.

Abstract: The arteries of monkeys given atherogenic diets develop marked intimal thickening and medial thinning, but luminal size apparently changes minimally. The hemodynamic significance of the atherosclerotic changes is therefore uncertain. To evaluate vascular function in atherosclerotic arteries, we studied the hind-limb vessels of adult male rhesus and cynomolgus monkeys to assess the structural and hemodynamic responses to an atherogenic diet given for about 1.5 years or for much longer periods (6.5 years for rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(44 citation statements)
references
References 22 publications
3
39
1
1
Order By: Relevance
“…10 Plaque growth initially leads to a compensatory arterial expansion ("positive remodeling") at sites of lesions, a response pattern that is well demonstrated in animal models of coronary disease. 11 The observation that luminal size is initially unaffected by plaque is well confirmed in necropsy studies in CLINICAL EPIDEMIOLOGY www.jasn.org human coronary arteries. 12 Yet the arterial remodeling process is bidirectional in nature.…”
Section: Relationship Between Imt and Indicators Of Vascular Remodelimentioning
confidence: 78%
“…10 Plaque growth initially leads to a compensatory arterial expansion ("positive remodeling") at sites of lesions, a response pattern that is well demonstrated in animal models of coronary disease. 11 The observation that luminal size is initially unaffected by plaque is well confirmed in necropsy studies in CLINICAL EPIDEMIOLOGY www.jasn.org human coronary arteries. 12 Yet the arterial remodeling process is bidirectional in nature.…”
Section: Relationship Between Imt and Indicators Of Vascular Remodelimentioning
confidence: 78%
“…65 However, the slow and unpredictable progression of atherosclerotic disease makes this impractical and ethically difficult, which emphasizes the importance of good animal models to study geometrical remodeling. Armstrong et al 66 were the first to report that the arterial wall adapts to experimentally induced plaque formation in primates. Two years later, Glagov et al confirmed their results in human cadaver studies, 2 promoting the notion of compensatory enlargement.…”
Section: Expansive Atherosclerotic Remodeling: What Did We Learn Frommentioning
confidence: 99%
“…9 Hypercholesterolemic macaque monkeys, rabbits, and pigs all show arterial compensatory enlargement, whereas highgrade stenosis or a decrease in lumen diameter is hardly ever observed. 10,11 Also, apoE-deficient (apoE Ϫ/Ϫ ) mice, the most frequently used atherosclerotic mouse model, show compensatory enlargement, and when they are fed an extremely high cholesterol diet or infused with angiotensin II, they even demonstrate aneurysm formation. 14 -17 Some apoE Ϫ/Ϫ mice do develop significant stenosis in the external CA but without evidence of ischemia.…”
mentioning
confidence: 99%